Polyphony and the Modern - Fruoco, Jonathan (Taylor & Francis, 2021)
"Polyphony and the Modern asks one fundamental question: what does it mean to be modern in one's own time? To answer that question, this volume focuses on polyphony as an index of modernity. In the Principle of Hope, Ernst Bloch showed that each moment in time is potentially fractured: people living in the same country can effectively live in different centuries - some making their alliances with the past and others betting on the future - but all of them, at least technically, enclosed in the temporal moment. But can a claim of modernity also mean something more ambitious? Can an artist, by accident or design, escape the limits of his or her own time, and somehow precociously embody the outlook of a subsequent age? This book sees polyphony as a bridge providing a terminology and a stylistic practice by which the period barrier between Medieval and Early Modern can be breached."